A kind of filling type hot melt adhesive and preparation method thereof

By copolymerizing bifunctional initiator and carboxylic acid monomer, combining modified polymers and plasticizers, high molecular weight hot melt adhesives were prepared, which solved the problem of reduced viscosity and poor fluidity of hot melt adhesives at low temperatures, and achieved high viscosity, good peel resistance and fluidity.

CN118460152BActive Publication Date: 2025-04-01SHENZHEN PROSPER DOBOND TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410566107.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-04-01
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

The existing hot melt adhesive loses its viscosity in low temperature environment, reduces the bonding strength, poor fluidity, is difficult to meet the requirements of slit filling, and is prone to aging and not resistant to solvent erosion.

Method used

By copolymerizing with bifunctional initiator and carboxylic acid monomer, a copolymer with high molecular weight and controllable molecular weight distribution is prepared, and modified polymers, plasticizers and antioxidants are added to improve the cohesive strength and fluidity of the hot melt adhesive.

Benefits of technology

The high viscosity, good peel resistance and fluidity of the hot melt adhesive are achieved, and its stability at low and high temperatures is enhanced, and the components are not obvious.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004829306490000101
    Figure BDA0004829306490000101
  • Figure BDA0004829306490000121
    Figure BDA0004829306490000121
  • Figure BDA0004829306490000131
    Figure BDA0004829306490000131
Patent Text Reader

Abstract

The present invention belongs to the technical field of adhesive preparation, and specifically relates to a filling hot melt adhesive and a preparation method thereof. The method comprises: 1) taking an acrylate monomer and an organic solvent, passing an inert gas to freeze, adding a bifunctional initiator, a catalyst, and a ligand, sealing a reaction container, cyclically deoxygenating and reacting at a constant temperature to obtain a macromolecular initiator; 2) taking a macromolecular initiator, an acrylate monomer, and a carboxylic acid monomer and dissolving them in an organic solvent, sealing a reaction container, cyclically deoxygenating and reacting at a constant temperature, and then settling and separating to obtain a copolymer; 3) adding a modified polymer, a plasticizer, and an antioxidant to the copolymer and mixing them evenly, evacuating until no bubbles are generated, cooling and drying to obtain a filling hot melt adhesive. The filling hot melt adhesive prepared by the present invention has high cohesive strength, viscosity, and good peeling resistance, and at the same time has good fluidity, penetrates into the slit to a large depth, and has certain application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive preparation, and particularly relates to a filled hot melt adhesive and a preparation method thereof. Background Art

[0002] Hot melt adhesive is an environmentally friendly adhesive with excellent bonding performance and stability. It is widely used in the textile industry, construction, petrochemical industry and other fields. Hot melt adhesive is thermoplastic, and its physical state changes with the change of temperature. It has a certain fluidity in the heated state, which is conducive to wetting the surface of the material. After the temperature drops, it cools and solidifies, providing good bonding strength. Hot melt adhesive has the advantages of fast initial bonding speed, good bonding ability, low use cost, and low volatility. However, commercially available hot melt adhesives are added with tackifying resins, modified polymers and other reagents. When applied to polar materials, the bonding strength is insufficient. And when the ambient temperature becomes low, the hot melt adhesive will lose its viscosity, resulting in a significant decrease in bonding strength. The hot melt adhesive modified with acrylic compounds has a longer service life, but the curing speed is slow, the fluidity becomes poor, and it is not conducive to wetting the material. The poor fluidity of hot melt adhesive will lead to an increase in the thickness of the bonding layer after curing, and because the hot melt adhesive has poor fluidity in the slit and the penetration depth is small, it cannot meet the requirements of slit filling.

[0003] Van der Waals forces will be generated between the hot melt adhesive and the bonded material. Van der Waals forces are divided into dispersion forces and polar forces, and polar forces are usually much greater than dispersion forces. The closer the polarity of the hot melt adhesive and the bonded material, the greater the physical adsorption force generated. According to technical research in this field, the bonding strength of polar materials and high-polarity hot melt adhesives is greater when they come into contact. In order to increase the polarity of polymers, the field usually uses the method of grafting polar functional groups, but not only is the grafting rate low, but the resulting hot melt adhesive is prone to aging and is not resistant to solvent erosion. If a tackifying resin with a stronger polarity is selected for physical blending, the performance improvement of the hot melt adhesive will be small.

[0004] Therefore, it is urgent to find a method for preparing hot melt adhesive that can improve the polarity and comprehensive performance of the hot melt adhesive and ensure that the hot melt adhesive has good fluidity. Summary of the invention

[0005] Based on the above content, in order to solve the problems of existing hot melt adhesives such as low temperature resistance, poor fluidity, and easy aging, the present invention proposes a filled hot melt adhesive and a preparation method thereof.

[0006] The objects of the present invention are:

[0007] 1. Improve the cohesive strength of the hot melt adhesive to ensure that the hot melt adhesive has high viscosity and good peeling resistance;

[0008] 2. Improve the fluidity of hot melt adhesive.

[0009] To achieve the above objectives, the present invention adopts the following technical solutions.

[0010] A method for preparing a filled hot melt adhesive.

[0011] The method comprises:

[0012] 1) taking an acrylic acid ester monomer and an organic solvent, introducing an inert gas to freeze them, adding a bifunctional initiator, a catalyst, and a ligand, sealing the reaction container, cyclically deoxygenating and reacting at a constant temperature to obtain a macromolecular initiator;

[0013] 2) dissolving a macromolecular initiator, an acrylate monomer, and a carboxylic acid monomer in an organic solvent, sealing a reaction vessel, cyclically deoxygenating and reacting at a constant temperature, and then settling and separating to obtain a copolymer;

[0014] 3) Adding the modified polymer, plasticizer and antioxidant to the copolymer and mixing them evenly, evacuating the mixture until no bubbles are generated, cooling and drying the mixture to obtain a filled hot melt adhesive.

[0015] As a preference,

[0016] Step 1) The acrylic acid ester monomer is lauryl methacrylate;

[0017] Step 1) The organic solvent is diethyl ether, and the amount thereof is 10-15 mL / mL of acrylate monomer;

[0018] Step 1) The inert gas is nitrogen, which is frozen at -205 to -200°C.

[0019] As a preference,

[0020] Step 1) The bifunctional initiator is ethylene glycol dibromoisobutyrate, and its usage is 0.01-0.02 mL / mL of acrylate monomer;

[0021] Step 1) The catalyst is cuprous bromide, and its dosage is 0.01-0.02 g / mL of acrylate monomer;

[0022] Step 1) The ligand is 4,4'-dinonyl-2,2'-bipyridine, and its usage is 0.02-0.04 g / mL acrylate monomer.

[0023] As a preference,

[0024] The isothermal reaction in step 1) is carried out at a temperature of -5 to 0°C for 7 to 8 hours.

[0025] As a preference,

[0026] The deoxygenation process in step 1) and step 2) is:

[0027] Freeze the solution at -205 to -200°C, evacuate for 5 to 8 minutes, and after stopping evacuation, slowly raise the temperature and introduce nitrogen to deoxygenate;

[0028] The deoxygenation in step 1) and step 2) is performed 3 to 4 times respectively.

[0029] As a preference,

[0030] Step 2) the macromolecular initiator, acrylate monomer and carboxylic acid monomer are prepared in a mass ratio of (0.2-0.5): (17.7-18.5): 10;

[0031] Step 2) the acrylic acid ester monomer is lauryl methacrylate;

[0032] Step 2) the carboxylic acid monomer is 2-methyleneglutaric acid;

[0033] Step 2) The organic solvent is NN-dimethylformamide, and 10 to 15 mL of the organic solvent is added per gram of the mixture of the macromolecular initiator, the acrylate monomer and the carboxylic acid monomer.

[0034] As a preference,

[0035] Step 2) The isothermal reaction is carried out at 130-140° C. for 5-6 hours.

[0036] As a preference,

[0037] Step 3) the modified polymer is a styrene-butyl acrylate block polymer, and the amount thereof is 0.2 to 0.3 g / g of copolymer;

[0038] Step 3) the plasticizer is diisononyl cyclohexane-1,2-dicarboxylate, and its usage is 0.6-0.8 mL / g copolymer;

[0039] Step 3) The antioxidant is 2,6-di-tert-p-cresol, and its dosage is 0.1-0.2 mL / g copolymer.

[0040] A filled hot melt adhesive.

[0041] Generally speaking, polymers with a wide molecular weight distribution are conducive to obtaining higher bonding strength. The viscosity is mainly provided by the low molecular weight part of the polymer with a wide molecular weight distribution, while the high molecular weight part provides the polymer with a higher cohesive strength, thereby ensuring that the polymer has a certain viscoelasticity. According to the research of those skilled in the art, the high molecular weight hot melt adhesive itself has a high viscosity and a large cohesive strength, which can effectively enhance its bonding strength, but the hot melt adhesive with too high molecular weight will lose viscosity due to excessive cohesive strength. The atom transfer radical polymerization method can regulate the molecular weight of the copolymer. In the technical solution of the present invention, the length and structure of the two-stage polymer are adjusted by the atom transfer radical polymerization method, and a large number of highly reactive free radicals in the polymerization system are reversibly deactivated to avoid chain transfer, chain termination and other reactions at any time, and to prepare a copolymer with high molecular weight and controllable molecular weight distribution.

[0042] At the same time, the cohesive strength of acrylic hot melt adhesives is usually low. In the art, the cohesive strength of acrylic hot melt adhesives is generally enhanced by adding a cross-linking agent. However, simply adding a cross-linking agent will cause uneven cross-linking of the hot melt adhesive, random copolymerization of the hot melt adhesive, and uncontrollable monomer composition, thereby resulting in excessive local cross-linking density and the generation of colloid particles. In order to avoid the above problems, the present invention prepares a bifunctional initiator based on acrylic compounds, and uses the macromolecule of the bifunctional initiator to initiate the copolymerization of the second monomer carboxylic acid monomer. In order to provide more active monomers to the copolymer and ensure that the monomer composition is controllable, the present invention prepares a bifunctional initiator containing terminal free radicals. Compared with the traditional initiator AIBN, the bifunctional initiator increases the polymerization reaction rate and conversion rate, and also shortens the polymerization reaction time. The present invention initiates the second monomer by a bifunctional initiator containing a terminal free radical, and uses cuprous bromide as a catalyst for chain extension. The copper complex system has a high affinity for halogens, a strong coordination effect with the ligand, and is conducive to the formation of a homogeneous system.

[0043] The main chain of acrylate does not contain a saturated double bond structure, while 2-methylene glutaric acid has a C=C double bond and -COOH. Its special structure makes it have many derivatives and can also participate in the polymerization of acrylic monomers. At the same time, the polymerization rate of 2-methylene glutaric acid monomer is significantly slower than that of lauryl methacrylate. The two asymmetric -COOH groups provide steric hindrance for the polymer, reduce the rate of active polymerization reaction, and significantly improve the monomer conversion rate. Acrylate monomers form hard segments, and carboxylic acid monomers form soft segments, which provide flexibility. After copolymerization, the molecular chains are not simply physically entangled to form physical crosslinking points to provide strength. In the absence of a crosslinking agent, the hot melt adhesive exhibits excellent adhesion. Under the condition of the same molecular weight of the copolymer, if the hard segment content is higher, the crystallinity of the soft segment molecular chain decreases with the increase of the hard segment content, resulting in poor fluidity of the soft segment and difficulty in obtaining an ordered crystal form. The prepared hot melt adhesive has a higher melt viscosity and better cohesive strength, but the peel strength is reduced. At high temperatures, acrylate monomers self-polymerize due to their high activity. Excessive acrylate monomers cause chain transfer, chain termination and other reactions in the system, and the viscosity of the system increases rapidly, which is not conducive to maintaining a homogeneous polymerization state.

[0044] When used, the hot melt adhesive is required to flow out at a faster speed. In order to improve the fluidity of the hot melt adhesive, the present invention is modified by a styrene-butyl acrylate block polymer. The styrene-butyl acrylate block polymer can be blended with a plasticizer, has good compatibility, provides a certain flexibility, and makes the molecular chain easy to move, which is manifested in that the hot melt adhesive can quickly wet the bonded material. In addition, there are two larger tert-butyl groups at the ortho position of the phenolic hydroxyl group in the sterically hindered phenolic antioxidant 2,6-di-tert-methyl cresol. By utilizing steric hindrance and a higher conjugated system, the free radicals generated after the chain transfer are stabilized. The copolymer enhances the double bond saturation of the styrene-butyl acrylate block polymer, and cooperates with 2,6-di-tert-methyl cresol to make the hot melt adhesive have good stability.

[0045] In addition, the present invention adds cyclohexane-1,2-dicarboxylic acid diisononyl ester with high polarizability, and cyclohexane-1,2-dicarboxylic acid diisononyl ester naphthenic oil plasticizer can swell the soft segment in the hot melt adhesive of the present invention, improve the fluidity of the hot melt adhesive, and make the hot melt adhesive have higher cohesive strength, viscosity, and peel strength. And the compatibility of cyclohexane-1,2-dicarboxylic acid diisononyl ester and the main copolymer is good. If the widely used phthalate plasticizer is used instead, although it is also an aromatic plasticizer with higher polarizability, it is obviously also suitable for the plasticization of high polarizability materials, but it has a benzene ring, and the plasticizing effect on the hard segment is stronger. After swelling, the physical crosslinking points of the hard segment are diluted, which has strong destructiveness to the network structure, and the cohesive strength of the hot melt adhesive is significantly reduced, showing extremely poor bonding strength and peel strength. In the test, it can be clearly seen that residual glue appears on the bonded material.

[0046] The beneficial effects of the present invention are as follows:

[0047] (1) The filled hot melt adhesive prepared by the present invention has high cohesive strength, viscosity and good peeling resistance;

[0048] (2) The filled hot melt adhesive prepared by the present invention has good fluidity and can penetrate into the slit to a large depth, thus having certain application prospects;

[0049] (3) The filled hot melt adhesive prepared by the present invention has uniform components and no obvious rubber particles;

[0050] (4) The filled hot melt adhesive prepared by the present invention has good stability. DETAILED DESCRIPTION

[0051] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0052] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0053] Example 1

[0054] A method for preparing a filled hot melt adhesive, the method comprising:

[0055] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate, 0.05 g of cuprous bromide, and 0.1 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0056] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:17.7:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0057] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0058] The performance of the filled hot melt adhesive obtained in this example was tested, and the testing method is as follows.

[0059] 1. Mechanical properties test:

[0060] Evenly apply the melted hot melt adhesive, the amount of adhesive applied is 28-32g / m 2 , place it at a temperature of 25℃ and a relative humidity of 50% for more than 1 hour to ensure that the hot melt adhesive is cured. Cut off a 25mm×180mm×0.5mm hot melt adhesive sample, clamp it in the clamp of the tensile testing machine, and keep the clamp horizontal. Start the tensile testing machine, and move the upper clamp upward at a speed of 2-3mm / min to test the tensile strength of the hot melt adhesive.

[0061] 2. Stickiness test:

[0062] Evenly apply the melted hot melt adhesive, the amount of adhesive applied is 28-32g / m 2 , place it at a temperature of 25℃ and a relative humidity of 50% for more than 1h to ensure that the hot melt adhesive is cured. Cut off a 25mm×180mm×0.5mm hot melt adhesive sample strip, place the sample at the center of one end of the test steel plate, and evenly roll and paste the sample within an area of ​​25mm×25mm with the weight of the roller without applying pressure. Keep the bonded sample vertically downward at a temperature of 25℃ and a relative humidity of 50%, clamp a 500g standard weight to the fixture, and record the time it takes for the sample to completely separate from the steel plate.

[0063] 3. Peel strength test:

[0064] Evenly coat the melted hot melt adhesive on the PET polar film, with the amount of adhesive being 28-32 g / m 2, place it at a temperature of 25℃ and a relative humidity of 50% for more than 1h to ensure that the hot melt adhesive is cured. Cut and remove a 25mm×180mm×0.5mm hot melt adhesive sample strip, paste the end of the sample on one end of the standard steel plate, hold the front end of the sample and ensure a certain tightness to keep the sample and the steel plate level, manually roll the roller back and forth in the direction of the sample for 3 times to avoid air residue, and continuously peel at a rate of 300mm / min using a peel force tester at a temperature of 25℃ and a relative humidity of 50%, and record the peel strength when the curve enters the plateau period.

[0065] In addition, the failure mode of tearing the tape off the adhered object is generally divided into cohesive failure and interface failure. Cohesive failure means that the cohesive strength of the hot melt adhesive is lower than the tear strength and interface bonding strength of the adhered material, and the fracture occurs from the inside. Interface failure means that the cohesive strength of the hot melt adhesive is higher than the tear strength and interface bonding strength of the adhered material, and there is no residual hot melt adhesive on the surface of the adhered material. Excessive cohesive strength will damage the adhered material. Record whether there is adhesive on the adhered material after peeling and whether the surface is damaged. If there is no adhesive and no damage marks, record "√", otherwise record "×".

[0066] 4. Stability test:

[0067] According to GB / T 16998-1997 Determination of Thermal Stability of Hot Melt Adhesives, take 100g of hot melt adhesive and keep it at a constant temperature of 180°C under an ambient humidity of 50%. Record the longest time that the hot melt adhesive can maintain viscosity when the skin turns black after oxidation and the viscosity changes by more than 10%.

[0068] Under an ambient humidity of 50%, take 100g of hot melt adhesive and keep it at a constant temperature of -10°C for 24 hours. If the hot melt adhesive remains sticky and does not crack, it is recorded as "√", otherwise it is recorded as "×".

[0069] The results are as follows.

[0070]

[0071] The filling hot melt adhesive prepared by the present invention has uniform components, no obvious glue particles, and good fluidity, which is convenient for extruding the hot melt adhesive and filling the slits. According to the results in the above table, it can be seen that the cured hot melt adhesive has a certain toughness, high peel strength and can maintain viscosity for a long time. Through experiments, it can be seen that the hot melt adhesive has a certain cohesive strength, there is no glue on the bonded material, and the surface is not damaged, indicating that the material will not suffer from cohesive damage, can well bond the material, and will not corrode the bonded material.

[0072] At 180°C, the hot melt adhesive did not oxidize until well over 70 hours later, indicating that the hot melt adhesive had good resistance to high temperature aging. At the same time, at a low temperature of -10°C, the hot melt adhesive had a certain viscosity and did not show obvious brittle cracking, indicating that the hot melt adhesive had a certain resistance to low temperatures. In general, the hot melt adhesive had high stability.

[0073] In addition, evenly apply the melted hot melt adhesive, with the amount of adhesive applied being 28-32 g / m 2 , placed at a temperature of 25°C and a relative humidity of 50% for more than 1 hour to ensure that the hot melt adhesive is solidified, and the sample strip is taken out for weighing. The sample strip is placed in water for 48 hours and then weighed to calculate the moisture content of the sample strip at this time. The result shows that the moisture content of the hot melt adhesive sample strip only increases by 0.1wt%. This shows that the hot melt adhesive has achieved a certain degree of solvent resistance.

[0074] Example 2

[0075] A method for preparing a filled hot melt adhesive, the method comprising:

[0076] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate, 0.05 g of cuprous bromide, and 0.1 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0077] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.1:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0078] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0079] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0080]

[0081] According to the results in the above table, the hot melt adhesive in this example still has excellent high temperature aging resistance. The polymerization rate of 2-methyleneglutaric acid monomer is significantly slower than that of lauryl methacrylate. The two asymmetric -COOH groups provide steric hindrance for the polymer, reduce the rate of active polymerization reaction, and significantly improve the monomer conversion rate. After copolymerization, the molecular chains are not simply physically entangled to form physical cross-linking points to provide strength. In the absence of a cross-linking agent, the hot melt adhesive exhibits excellent adhesion. Since the monomer conversion rate of the hot melt adhesive in this example is higher, the hot melt adhesive exhibits higher cohesive strength and bonding strength.

[0082] Example 3

[0083] A method for preparing a filled hot melt adhesive, the method comprising:

[0084] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate, 0.05 g of cuprous bromide, and 0.1 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0085] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.5:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0086] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0087] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0088]

[0089] According to the results in the above table, compared with Example 2, since the content of the soft segment of the hot melt adhesive in this example is higher, the 2-methylene glutaric acid monomer forms a soft segment, which provides flexibility for the hard segment formed by the lauryl methacrylate monomer. Therefore, the hot melt adhesive in this example shows greater flexibility, but the molecular chain slips, the tensile resistance of the obtained hot melt adhesive decreases, and the bonding strength is reduced. In order to take into account both mechanical properties and bonding strength, the present invention controls the amount of 2-methylene glutaric acid added, while ensuring a high monomer conversion rate, regulating the bonding strength, cohesive strength and peel strength of the hot melt adhesive. In addition, the filled hot melt adhesive in the embodiment of the present invention has good fluidity and stability, and has good prospects in narrow gap filling.

[0090] Comparative Example 1

[0091] A method for preparing a filled hot melt adhesive, the method comprising:

[0092] 1) lauryl methacrylate and 2-methyleneglutaric acid were prepared in a mass ratio of 18.3:10, 10 mL of NN-dimethylformamide was added to the mixture of lauryl methacrylate and 2-methyleneglutaric acid per gram, 0.01 mL of ethylene glycol dibromoisobutyrate, 0.01 g of cuprous bromide, and 0.2 g of 4,4'-dinonyl-2,2'-bipyridine were added to each milliliter of lauryl methacrylate, the reaction container was sealed, the solution was frozen by liquid nitrogen at -205°C, vacuumed for 5 minutes, the vacuum was stopped, the temperature was slowly raised and nitrogen was introduced to remove oxygen and the cycle was repeated 4 times, the copolymer was precipitated and separated after being kept at a constant temperature of 140°C for 5 hours;

[0093] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0094] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0095]

[0096]

[0097] Generally speaking, polymers with a wide molecular weight distribution are conducive to obtaining higher bonding strength. The viscosity is mainly provided by the low molecular weight part of the polymer with a wide molecular weight distribution, while the high molecular weight part provides the polymer with a higher cohesive strength, thereby ensuring that the polymer has a certain viscoelasticity. According to the results in the above table, in this example, the polymer is formed by continuously adding and catalyzing highly reactive free radical structural units. The polymerization reaction rate is fast and occurs continuously. Chain transfer, chain termination and other reactions occur at any time in the system. The polymer molecular weight is super high and uncontrollable. Therefore, the molecular weight of the hot melt adhesive in this example is too high, the cohesive strength is too large, it is easy to separate from the bonded material, and there are glue particles and uneven components, which hinder the fluidity of the hot melt adhesive.

[0098] Comparative Example 2

[0099] A method for preparing a filled hot melt adhesive, the method comprising:

[0100] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate and 0.15 g of benzoyl peroxide, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0101] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.1:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0102] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0103] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0104]

[0105] According to the results in the above table, this example uses organic peroxide as a crosslinking agent. Organic peroxide decomposes upon heating to generate free radicals, which attack the hydrogen atoms on the C=C double bond or add to the double bond, so that the monomer macromolecule forms new free radicals. The decomposition rate of peroxide is fast, and the crosslinking reaction speed is fast. However, simply adding a crosslinking agent will cause uneven crosslinking of the hot melt adhesive, random copolymerization of the hot melt adhesive, and uncontrollable monomer composition, which will lead to excessive local crosslinking density and the generation of rubber particles.

[0106] This shows that the method in which the macromolecule of the bifunctional initiator initiates the copolymerization of the second monomer, the carboxylic acid monomer, is very important, which not only provides more active monomers for the copolymer, but also ensures that the monomer composition is controllable.

[0107] Comparative Example 3

[0108] A method for preparing a filled hot melt adhesive, the method comprising:

[0109] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of azobisisobutyronitrile, 0.01 g of cuprous bromide, and 0.2 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0110] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.1:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0111] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0112] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0113]

[0114] According to the results in the above table, since the initiator azobisisobutyronitrile does not promote the polymerization reaction rate as well as dibromoisobutyric acid glycol ester selected in the present invention, the monomer conversion rate is low, and the molecular chains are physically entangled after copolymerization to form physical cross-linking points to provide strength, the bonding strength of the hot melt adhesive in this example is reduced.

[0115] Comparative Example 4

[0116] A method for preparing a filled hot melt adhesive, the method comprising:

[0117] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate, 0.05 g of cuprous bromide, and 0.1 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0118] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.1:8, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0119] 3) Prepare copolymer, styrene-butyl acrylate block polymer, diisononyl cyclohexane-1,2-dicarboxylate and 2,6-di-tert-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0120] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0121]

[0122]

[0123] According to the results in the above table, it can be analyzed that when the molecular weight of the copolymer is the same, if the hard segment content is higher, the crystallinity of the soft segment molecular chain decreases with the increase of the hard segment content, resulting in poor fluidity of the soft segment and difficulty in obtaining an ordered crystal form. The prepared hot melt adhesive has a higher melt viscosity and better cohesive strength, but the peel strength decreases.

[0124] Comparative Example 5

[0125] A method for preparing a filled hot melt adhesive, the method comprising:

[0126] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate, 0.05 g of cuprous bromide, and 0.1 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0127] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.1:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0128] 3) The copolymer and diisononyl cyclohexane-1,2-dicarboxylate were prepared in a ratio of 1 g:0.6 mL and mixed evenly, vacuumed until no bubbles were generated, cooled and dried to obtain a filled hot melt adhesive.

[0129] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0130]

[0131] The hot melt adhesive in this example has particles, poor fluidity, and significantly slows down the speed of wetting the bonded material. According to the results in the above table, the stability of the hot melt adhesive in this example at high and low temperatures is significantly reduced. This is because the styrene-butyl acrylate block polymer can be blended with the plasticizer, has good compatibility, provides a certain degree of flexibility, and makes the molecular chain easy to move. At the same time, there are two large tert-butyl groups at the ortho position of the phenolic hydroxyl group in 2,6-di-tert-butyl phenol. The free radicals generated after chain transfer are stabilized by steric hindrance and a higher conjugated system. The copolymer enhances the double bond saturation of the styrene-butyl acrylate block polymer, and cooperates with 2,6-di-tert-butyl phenol to make the hot melt adhesive have good stability.

[0132] Comparative Example 6

[0133] A method for preparing a filled hot melt adhesive, the method comprising:

[0134] 1) Take 5 mL of lauryl methacrylate and 50 mL of ether, introduce nitrogen, freeze with liquid nitrogen at -205°C, add 0.05 mL of ethylene glycol dibromoisobutyrate, 0.05 g of cuprous bromide, and 0.1 g of 4,4'-dinonyl-2,2'-bipyridine, seal the reaction container, freeze the solution with liquid nitrogen at -205°C, evacuate for 5 min, stop evacuating, slowly raise the temperature and introduce nitrogen to remove oxygen, and cycle 4 times, keep constant temperature at 0°C for 8 h to obtain a macromolecular initiator;

[0135] 2) preparing a macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid in a mass ratio of 0.2:18.1:10, adding 10 mL of NN-dimethylformamide per gram of the mixture of the macromolecular initiator, lauryl methacrylate and 2-methyleneglutaric acid, sealing the reaction container, freezing the solution with liquid nitrogen at -205°C, evacuating the solution for 5 minutes, slowly heating the solution and introducing nitrogen to remove oxygen after stopping the evacuation, and circulating the mixture for 4 times, maintaining the mixture at a constant temperature of 140°C for 5 hours, and separating the mixture to obtain a copolymer;

[0136] 3) Prepare copolymer, styrene-butyl acrylate block polymer, phthalate, and 2,6-di-tert-p-cresol in a ratio of 1 g: 0.2 g: 0.6 mL: 0.1 mL and mix well, evacuate until no bubbles are generated, cool and dry to obtain a filled hot melt adhesive.

[0137] The filled hot melt adhesive obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.

[0138]

[0139] According to the results in the above table, it can be seen that the mechanical properties of the hot melt adhesive in this example have not been greatly reduced, but it shows poor stickiness, peel strength, cohesive strength and stability. This is because the high polarizability cyclohexane-1,2-dicarboxylic acid diisononyl ester used in the present invention, cyclohexane-1,2-dicarboxylic acid diisononyl ester naphthenic oil plasticizer can swell the soft segment in the hot melt adhesive of the present invention, improve the fluidity of the hot melt adhesive, and make the hot melt adhesive have higher cohesive strength, viscosity, and peel strength. And the compatibility of cyclohexane-1,2-dicarboxylic acid diisononyl ester and the main copolymer is good. If the widely used phthalate plasticizer is used instead, because it has a benzene ring, the plasticizing effect on the hard segment is stronger, and the physical crosslinking points of the hard segment are diluted after swelling, which has a strong destructive effect on the network structure, and the cohesive strength of the hot melt adhesive will be significantly reduced, showing extremely poor bonding strength and peel strength. In the test, it can be clearly seen that residual glue appears on the bonded material.

[0140] Application Examples

[0141] According to the operation of the embodiment, a filled hot melt adhesive is prepared.

[0142] Choose a certain brand of hot melt adhesive.

[0143] The hot melt adhesive is tested for performance, and the testing method is as follows.

[0144] 1. Penetration depth:

[0145] Score a 1mm wide and 1cm deep slit on a transparent acrylic plate, take 0.3g of hot melt adhesive and heat it to 180℃ to ensure that the hot melt adhesive is completely melted, quickly cover the slit with the hot melt adhesive and let it flow naturally. After 3 minutes, use a light to ensure that the hot melt adhesive is solidified. Cut the transparent acrylic plate 1mm away from the slit and measure the penetration depth of the hot melt adhesive.

[0146] The results are as follows.

[0147] 2. Fracture toughness:

[0148] Take two other acrylic sheets and evenly apply the melted hot melt adhesive on the edge of one acrylic sheet. The coating width is 5 cm and the amount of adhesive is 28-32 g / m 2 , another acrylic sheet is horizontally covered on it, with a covering area of ​​5cm×15cm, and placed at a temperature of 25℃ and a relative humidity of 50% for more than 1h to ensure that the hot melt adhesive is cured. The critical load of the model when it breaks is measured on a mechanical properties testing machine using a three-point or four-point bending method, and its fracture toughness is calculated based on the size of the covering, the thickness of the hot melt adhesive at the covering, and the span between the two supporting points of the model.

[0149] The results are as follows.

[0150]

[0151] According to the results in the above table, the filled hot melt adhesive prepared by the present invention has good fluidity. Compared with the commercially available hot melt adhesive, it penetrates deeper into the slit and can fill more than 90% of the slit. Under certain adhesive thickness and width, it is found through experiments that the heat resistance of the material remains basically unchanged, and the fracture toughness of the hot melt adhesive is significantly improved, which has a good prospect in the field of adhesives.

Claims

1. A method for preparing a filled hot melt adhesive, characterized in that: The method comprises: 1) Take acrylate monomers and organic solvents, introduce inert gas to freeze, add bifunctional initiator, catalyst, ligand, seal the reaction container, circulate deoxygenation and react at constant temperature to obtain macromolecular initiator; 2) Take the macromolecular initiator, acrylate monomer, and carboxylic acid monomer and dissolve them in an organic solvent, seal the reaction container, circulate deoxygenation and react at a constant temperature, then settle and separate to obtain a copolymer; 3) Adding modified polymer, plasticizer and antioxidant to the copolymer and mixing evenly, evacuating until no bubbles are generated, cooling and drying to obtain a filled hot melt adhesive; Step 2) the carboxylic acid monomer is 2-methyleneglutaric acid; Step 3) The modified polymer is a styrene-butyl acrylate block polymer, and the amount used is 0.2-0.3 g / g copolymer.

2. The method for preparing a filled hot melt adhesive according to claim 1, characterized in that: Step 1) the acrylic acid ester monomer is lauryl methacrylate; Step 1) the organic solvent is diethyl ether, and the amount used is 10-15 mL / mL of acrylate monomer; Step 1) The inert gas is nitrogen, which is frozen at -205 to -200 °C.

3. The method for preparing a filled hot melt adhesive according to claim 1, characterized in that: Step 1) the bifunctional initiator is ethylene glycol dibromoisobutyrate, and the amount used is 0.01-0.02 mL / mL of acrylate monomer; Step 1) The catalyst is cuprous bromide, and the amount used is 0.01-0.02 g / mL of acrylate monomer; Step 1) The ligand is 4,4'-dinonyl-2,2'-bipyridine, and its usage is 0.02-0.04 g / mL acrylate monomer.

4. A method for preparing a filled hot melt adhesive according to claim 1, 2 or 3, characterized in that: The isothermal reaction in step 1) is carried out at a temperature between -5 and 0°C for 7 to 8 hours.

5. The method for preparing a filled hot melt adhesive according to claim 1, characterized in that: The deoxygenation process in step 1) and step 2) is: Freeze the solution at -205 to -200 °C, evacuate for 5 to 8 min, and then slowly raise the temperature and introduce nitrogen to deoxygenate after stopping evacuation. The deoxygenation in step 1) and step 2) is performed 3 to 4 times respectively.

6. The method for preparing a filled hot melt adhesive according to claim 1, characterized in that: Step 2) the macromolecular initiator, acrylate monomer and carboxylic acid monomer are prepared in a mass ratio of (0.2-0.5): (17.7-18.5): 10; Step 2) the acrylic acid ester monomer is lauryl methacrylate; Step 2) The organic solvent is NN-dimethylformamide, and 10 to 15 mL of the organic solvent is added per gram of the mixture of the macromolecular initiator, the acrylate monomer and the carboxylic acid monomer.

7. A method for preparing a filled hot melt adhesive according to claim 1 or 6, characterized in that: Step 2) The isothermal reaction is carried out at 130-140°C for 5-6 hours.

8. The method for preparing a filled hot melt adhesive according to claim 1, characterized in that: Step 3) the plasticizer is diisononyl cyclohexane-1,2-dicarboxylate, and the amount thereof is 0.6-0.8 mL / g copolymer; Step 3) The antioxidant is 2,6-di-tert-p-cresol, and the amount used is 0.1-0.2 mL / g copolymer.

9. A filled hot melt adhesive prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Non-woven felt with reduced transmittance and increased caliper size

    CN114787439A

  • Highly transparent acrylic copolymer, method for producing the same and application thereof

    JP2002080548A